2015
DOI: 10.4103/1673-5374.158351
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of kinesin-5 improves regeneration of injured axons by a novel microtubule-based mechanism

Abstract: Microtubules have been identified as a powerful target for augmenting regeneration of injured adult axons in the central nervous system. Drugs that stabilize microtubules have shown some promise, but there are concerns that abnormally stabilizing microtubules may have only limited benefits for regeneration, while at the same time may be detrimental to the normal work that microtubules perform for the axon. Kinesin-5 (also called kif11 or Eg5), a molecular motor protein best known for its crucial role in mitosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…This causes a G2/M arrest, which may induce apoptosis [24,40]. Non-mitosis-related functions of KIF11 include neuronal growth cone extension, navigation, and migration [41]. Our demonstration that KIF11 mRNA and protein levels increased with meningioma WHO grade and that higher mRNA levels of KIF11 were related to shorter progression-free survival, is consistent with prior literature reports in other cancer types [24,42,43,44,45,46].…”
Section: Discussionmentioning
confidence: 99%
“…This causes a G2/M arrest, which may induce apoptosis [24,40]. Non-mitosis-related functions of KIF11 include neuronal growth cone extension, navigation, and migration [41]. Our demonstration that KIF11 mRNA and protein levels increased with meningioma WHO grade and that higher mRNA levels of KIF11 were related to shorter progression-free survival, is consistent with prior literature reports in other cancer types [24,42,43,44,45,46].…”
Section: Discussionmentioning
confidence: 99%
“…Axons presumably grow faster when either of these motors is inhibited because of greater mobility of short microtubules and also less compressive force on the longer microtubules 24 . A potential issue with KIF11 inhibition as therapy for nerve injury arises from studies indicating that axon navigation is impaired when KIF11 is suppressed 25 , because of KIF11’s role in regulating the amount of microtubule sliding into the growth cone. It was reported that KIF15 works as a tetramer 12,26 , similar to KIF11 27 , and is believed to be capable of cross-linking microtubules and switching microtubule tracks, while other work suggests that it acts as a dimer 28 .…”
Section: Discussionmentioning
confidence: 99%
“…One of the long-standing mysteries of the microtubule transport data is why only short microtubules undergo rapid concerted transport down the axon. We previously considered it reasonable that long microtubules are stationary because multiple dynein molecules could presumably interface between the two microtubules, some with their motor domains interacting with the first microtubule and others with their motor domains interacting with the other microtubule [55]. Thus, the forces would cancel out, leading to non-movement of long microtubules.…”
Section: Cross-linker Proteinsmentioning
confidence: 99%